Abnormal Expression of DNA Double-Strand Breaks Related Genes, ATM and GammaH2AX, in Thyroid Carcinoma - Jin-lin Hu; Si-si Hu; Xiu-xiu Hou; Xin Zhu; Jun Cao; Lie-hao Jiang; Ming-hua Ge (International Journal of Endocrinology)
ATM and γH2AX play a vital role in the detection of DNA double-strand breaks (DSB) and DNA damage response (DDR). This study aims to investigate ATM and γH2AX expression in thyroid cancer and discuss possible relationship between thyroid function tests and DNA damage. The expression of ATM and γH2AX was detected by immunohistochemistry in 30 cases of benign nodular goiter, 110 cases of well differentiated thyroid cancer, 22 cases of poorly differentiated thyroid cancer, and 21 cases of anaplastic thyroid cancer. Clinicopathological features, including differentiation stages, distant metastasis, lymph node metastasis, T classification, TNM stage, and tests of thyroid functions (TPOAb, Tg Ab, T3, FT3, T4, FT4, TSH, and Tg), were reviewed and their associations with γH2AX and ATM were analyzed. γH2AX and ATM expressed higher in thyroid cancer tissues than in benign nodular goiter and normal adjacent tissues. γH2AX was correlated with ATM in thyroid cancer. Both γH2AX and ATM expression were associated with FT3. γH2AX was also associated with T classification, TNM stage, FT4, TSH, and differentiation status. Therefore both of ATM and γH2AX seem to correlate with thyroid hormones and γH2AX plays a role in the differentiation status of thyroid cancer.